IMPLEMENTASI AI PADA SISTEM INFOMASI MANAJEMEN ERA DIGITAL - Silitonga, Arino Fanther; Jhon Kristopel Manalu; Darwis Manalu (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of digital technology today has driven a significant transformation in information management, one of which is the application of artificial intelligence in management information systems, providing effectiveness and efficiency in business processes. The integration of artificial intelligence and management information systems has changed the procedures for collecting data, analyzing data, and utilizing data and the organizational decision-making process. Management Information Systems (MIS) have become a strategic element that integrates data, technology, and processes to support organizational competitiveness. This research aims to provide an understanding of the concept, benefits, and role of MIS in supporting digital transformation. Through this research, it is expected to provide insights and knowledge about the role of MIS in supporting managerial functions such as planning, organizing, controlling, and speed in decision-making. The existence of MIS can support organizational performance to achieve organizational goals in the current digital era.